Carrier for electrostatic latent image developer and manufacturing method thereof, two-component developer, replenishment developer, process cartridge, image forming apparatus, and image forming method
Patent Information
- Application Number
- JP2020113364
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-06-30
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2040-06-30
AI Technical Summary
【0007】 本発明によると、キャリア同士の凝集及び経時のベタ画像におけるベタキャリア付着を抑制できる静電潜像現像剤用キャリアを提供することができる。
Smart Images

Figure 0007631685000003 
Figure 0007631685000004 
Figure 0007631685000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a carrier for an electrostatic latent image developer and a manufacturing method thereof, a two-component developer, a replenishment developer, a process cartridge, an image forming apparatus, and an image forming method. [Background technology]
[0002] In the electrophotographic method, an electrostatic latent image is formed on the surface of a photoreceptor using a charging and exposure means, the electrostatic latent image is then developed with a developer containing a magnetic carrier and a toner to obtain a toner image, and the toner image is then transferred to a transfer member and fixed to obtain a visible image.
[0003] The electrophotographic method is now being used not only in copying machines, which have been widely used up until now, but also in production printing, which can print high-definition images at higher speeds, and therefore there has been a demand for developers that can meet the demands for higher image quality and faster image output.
[0004] As a carrier for use in such a developer, a carrier in which magnetic core particles are coated with a resin to stabilize the charging characteristics has been proposed (for example, Patent Document 1). In addition, a carrier in which the chargeability of the carrier is adjusted by controlling the amount of a charge control agent disposed on the carrier surface has been proposed (for example, Patent Document 2). Summary of the Invention [Problem to be solved by the invention]
[0005] An object of the present invention is to provide a carrier for an electrostatic latent image developer that can suppress carrier aggregation and solid carrier adhesion in a solid image over time. Incidentally, suppressing the solid image carrier adhesion means that the number of carrier particles adhering to a solid image after image formation over a long period of time is small. [Means for solving the problem]
[0006] The electrostatic latent image developer carrier of the present invention as a means for solving the above problems is A carrier for an electrostatic latent image developer, comprising: a magnetic core particle; and a coating layer that coats at least a portion of the surface of the core particle, The electrostatic latent image developer carrier is characterized in that it contains a compound having a boiling point of 110°C to 230°C. Effect of the Invention
[0007] According to the present invention, it is possible to provide a carrier for an electrostatic latent image developer that can suppress the aggregation of carrier particles and the adhesion of solid carrier particles to a solid image over time. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 is a schematic view showing an example of a process cartridge of the present invention. [Diagram 2] FIG. 2 is a schematic diagram showing an example of an image forming apparatus according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] (Electrostatic latent image developer carrier) The carrier for electrostatic latent image developer of the present invention (hereinafter also referred to as "carrier") has core particles and a coating layer (hereinafter also referred to as "coating film", "coat layer", "coat film", or "carrier coat layer"), and further has other components as necessary. The carrier for the electrostatic latent image developer contains a compound having a boiling point of 110°C to 230°C. The coating layer covers at least a portion of the surface of the core particle.
[0010] Carriers used in production printing are required to be able to handle higher image quality and faster image output, and such carriers must have both a certain level of strength in magnetic force and electrical resistance. In general, magnetic particles used in core materials (core material particles) tend to have a lower electrical resistance when their saturation magnetization is increased. In other words, there is a trade-off between electrical resistance and saturation magnetization. Therefore, in order to achieve both, a carrier has been proposed in which the core material is covered with a coating layer such as a resin. However, when a carrier is used for a long time, the coating layer covering the core material may be worn away, exposing the core material. If a material with high saturation magnetization is used for the core material, the electrical resistance of the entire carrier may decrease due to the exposed core material, which may result in solid carrier adhesion.
[0011] In view of this, carriers have been proposed in which the durability of the coating film is improved by increasing the thickness of the coating film or by incorporating inorganic fine particles in the coating film. However, these proposals mean that there are areas with thin and thick coating film thicknesses within a single carrier, and these areas with thin coating film thickness become leak areas, lowering resistance, making it difficult to improve solid carrier adhesion and making it difficult to meet the demand for even higher image quality.
[0012] Therefore, the present inventors have conducted research into carriers that can withstand high image quality. As a result, it was found that a carrier that can withstand high image quality is a carrier that can suppress the occurrence of carrier aggregation and solid carrier adhesion, and that such a carrier is a carrier with minimal unevenness in the coating layer (the unevenness in the coating layer is flattened). Next, the inventors of the present invention investigated a method for reducing the unevenness of the coating layer. As a result, they noticed that by using a solvent with a relatively high boiling point when forming the coating layer, the material of the coating layer can be dried in a state in which it is sufficiently wet and spread over the surface of the core particle. They then found that the thickness of the coating layer can be made uniform by drying the material of the coating layer in a state in which it is sufficiently wet and spread over the surface of the core particle, and thus completed the present invention.
[0013] <Core particles> The core particles are not particularly limited as long as they are magnetic core particles, and can be appropriately selected according to the purpose. The core particles can be appropriately selected from known two-component carriers for electrophotography according to the purpose, and include, for example, ferromagnetic metals such as iron and cobalt; iron oxides such as magnetite, hematite, and ferrite; various alloys or compounds; and resin particles in which these magnetic materials are dispersed in resin. These may be used alone or in combination of two or more. Among these, Mn-based ferrite, Mn-Mg-based ferrite, and Mn-Mg-Sr ferrite are preferred from the viewpoint of environmental friendliness.
[0014] The core particles may be either appropriately synthesized or commercially available. The core particles may be synthesized, for example, by the following method. The raw materials are mixed in appropriate amounts to satisfy the composition formula: MFe2O4 (M: containing at least one selected from Mn, Mg, Li, Ca, Sr, Cu, and Zn), water, binder, and dispersant are added, the solid ratio is adjusted, and the mixture is pulverized in a wet ball mill, mixed, and dried. Next, the mixture is heated at 700°C to 1,100°C, and the slurry pulverized in the wet ball mill is granulated and dried. Next, a sintering furnace capable of controlling the oxygen concentration is used, and the mixture is kept at a sintering temperature of 1,000°C to 1,300°C for 1 to 24 hours, after which it is crushed and the particle size is adjusted to obtain core particles.
[0015] The BET specific surface area of the core particles is 0.27 m 2 / g~0.31m 2 / g, 0.28m 2 / g~0.30m 2 / g is preferred. The BET specific surface area is 0.27 m 2 / g~0.31m 2 When the toner particle diameter is 100 / g, the resin of the coating layer and the core particles are strongly bonded to each other, the coating layer is not scraped off, the carrier resistance is prevented from decreasing, the toner is not damaged, and the resistance is prevented from increasing due to toner spent. The BET specific surface area is 0.27 m 2If the BET specific surface area is less than 0.31 m / g, the binding strength between the resin of the coating layer (carrier coat film) and the core particles is low, and the carrier coat film is easily scraped over time, which may cause a decrease in carrier resistance. 2 If it exceeds 1 / g, the toner is easily damaged, and an increase in resistance due to toner spent may occur. The BET specific surface area can be adjusted by the firing temperature during production of the core particles. The BET specific surface area can be measured by a known method.
[0016] <Compound> The compound also serves as a solvent for the coating layer liquid described below (hereinafter, the "compound" will be referred to as the "solvent"). The boiling point of the solvent is 110°C to 230°C, more preferably 140°C to 220°C, and even more preferably 140°C to 200°C. If the boiling point of the solvent is less than 110°C, when the coating layer is formed on the core material particles, the coating layer liquid dries quickly and dries without spreading on the core material, which may cause the surface of the coating layer to become rough and the unevenness of the coating layer to become large. If the boiling point of the solvent is more than 230°C, when the coating layer is formed on the core material particles, the drying of the coating layer liquid is suppressed and the coating layer spreads on the core material particles, but the drying is suppressed too much, which may cause aggregation with nearby core material particles.
[0017] The boiling point of the solvent in the coating layer can be measured, for example, as follows. 50 mg of the carrier is filled into a special cup and inserted into a GCMS (QP-2010, manufactured by Shimadzu Corporation) for measurement. The compounds contained in the carrier can be qualified by analyzing the obtained chromatograph. Furthermore, the compounds that have been qualified are sampled in a sample container with a pinhole, and this is measured using a DSC (DSC7000, Hitachi High-Tech Science Corporation) by raising the temperature at a constant rate up to a temperature higher than the end of evaporation, and the boiling point is determined from the endothermic peak due to evaporation.
[0018] The solvent having a boiling point of 110°C to 230°C is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include toluene (boiling point: 111°C), butyl acetate (boiling point: 126°C), isobutyl acetate (boiling point: 118°C), octane (boiling point: 125°C), diethylbenzene (boiling point: 184°C), xylene (boiling point: 144°C), butyl cellosolve (boiling point: 171°C), decane (boiling point: 174°C), dodecane (boiling point: 216°C), etc. These may be used alone or in combination of two or more. Among these, when a silicone resin is used as the resin described below, hydrocarbons (toluene, octane, xylene, decane, dodecane) are preferred.
[0019] The content of the solvent having a boiling point of 110° C. to 230° C. is preferably 0.50 μg or less per 1 g of the carrier. When the content is 0.50 μg or less, the strength of the coating film becomes appropriate, and the problem of the film strength being weakened and being disadvantageous against scraping can be prevented. The content may be 0.005 μg or more. The content of the compound (solvent) in the coating layer can be measured, for example, as follows. Standard solutions containing 1.0 mass %, 0.01 mass %, and 0.001 mass % of the compound (solvent) in acetone are prepared. Each of these standard solutions is inserted into a GCMS (QP-2010, manufactured by Shimadzu Corporation) and the peak area of each standard solution is measured. In this way, a correlation equation between the compound content and peak area is obtained. Furthermore, 50 mg of carrier is filled into a dedicated cup and inserted into a GCMS (QP-2010, manufactured by Shimadzu Corporation) to obtain the peak area of the compound in the carrier. The peak area value of the compound in the carrier can be applied to the correlation equation between the compound content and peak area to calculate the compound content in the carrier.
[0020] <Coating layer> The coating layer covers at least a portion of the surface of the core particle, and preferably covers the entire surface of the core particle (no defective portions of the coating layer). The coating layer preferably contains a resin, more preferably contains inorganic fine particles as required, and further contains other components as required.
[0021] <<Resin>> The resin is not particularly limited as long as it can impart the necessary electrostatic property, and can be appropriately selected according to the purpose, and examples thereof include silicone resin, acrylic resin, etc. These can be used alone or in combination of two or more kinds. Among these, it is preferable to use a silicone resin and an acrylic resin in combination. The acrylic resin has strong adhesiveness and low brittleness, and therefore has excellent abrasion resistance. However, since the acrylic resin has high surface energy, when it is used in combination with a toner that is prone to being spent (easily adhered to the carrier), problems such as a decrease in the charge amount due to the accumulation of the spent toner component (toner that adheres to the carrier) may occur. The silicone resin has a low surface energy, so that the toner components are not easily spent, and the accumulation of the spent components that causes the film to be scraped is not easily promoted. However, the silicone resin has a low adhesiveness and is highly brittle, so that the abrasion resistance may be deteriorated. Therefore, by using an acrylic resin and a silicone resin in combination, it is possible to obtain a coating layer that is resistant to spent and has abrasion resistance.
[0022] The silicone resin is not particularly limited and may be selected from known silicone resins according to the purpose. Examples of the silicone resin include straight silicone resins consisting of organosiloxane bonds only, and modified silicone resins modified with alkyd, polyester, epoxy, acrylic, urethane, etc. The silicone resin may be a synthetic product or a commercially available product. Commercially available straight silicone resins include KR271, KR255, KR152 (all manufactured by Shin-Etsu Chemical Co., Ltd.), SR2400, SR2406, and SR2410 (all manufactured by Toray Dow Corning Silicone Co., Ltd.). These may be used as a single silicone resin, or may be used together with other crosslinking components, charge control components, and the like. Commercially available modified silicone resins include KR206 (alkyd modified), KR5208 (acrylic modified), ES1001N (epoxy modified), KR305 (urethane modified) (all manufactured by Shin-Etsu Chemical Co., Ltd.), SR2115 (epoxy modified), and SR2110 (alkyd modified) (all manufactured by Toray Dow Corning Silicone Co., Ltd.).
[0023] The acrylic resin is not particularly limited as long as it contains an acrylic component, and can be appropriately selected depending on the purpose. The acrylic resin may be used alone, but it is also possible to use at least one or more other components that undergo crosslinking reaction at the same time. The other components that undergo crosslinking reaction are not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include amino resins and acid catalysts. The amino resins are not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include guanamine and melamine resins. The acid catalysts are not particularly limited as long as they have a catalytic effect, and can be appropriately selected depending on the purpose, and examples thereof include those having reactive groups such as fully alkylated type, methylol group type, imino group type, and methylol / imino group type.
[0024] <<Inorganic fine particles>> The inorganic fine particles are not particularly limited and can be appropriately selected depending on the purpose. For example, barium sulfate is preferred for imparting durability and antistatic properties to the coating layer. To provide the coating layer with durability and resistance properties, conductive fine particles are preferred. Examples of the conductive fine particles include fillers in which tin dioxide or indium oxide is formed as a layer on a substrate, and carbon black. Examples of the substrate include aluminum oxide, titanium dioxide, zinc oxide, silicon dioxide, zirconium oxide, and the like, with aluminum oxide and titanium dioxide being preferred. In addition to the above, aluminum oxide, titanium dioxide, zinc oxide, silicon dioxide, zirconium oxide, etc. may also be used. By including inorganic fine particles in the coating layer, it is possible to prevent the core material from being exposed due to loss of the carrier coat film caused by long-term running, resulting in a sudden drop in resistance and deterioration of solid carrier adhesion.
[0025] The volume average particle size of the inorganic fine particles is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 0.3 μm to 0.7 μm. The content of the inorganic fine particles is not particularly limited and can be appropriately selected depending on the purpose.
[0026] <<Other ingredients>> The other components are not particularly limited and may be appropriately selected depending on the purpose. Examples of the other components include a silane coupling agent and a condensation polymerization catalyst.
[0027] The silane coupling agent is preferably contained in order to stably disperse the inorganic fine particles. The silane coupling agent is not particularly limited, but examples thereof include r-(2-aminoethyl)aminopropyltrimethoxysilane, r-(2-aminoethyl)aminopropylmethyldimethoxysilane, r-methacryloxypropyltrimethoxysilane, N-β-(N-vinylbenzylaminoethyl)-r-aminopropyltrimethoxysilane hydrochloride, r-glycidoxypropyltrimethoxysilane, r-mercaptopropyltrimethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, vinyltriacetoxysilane, r-chloropropyltrimethoxysilane, hexamethyldisilazane, r-anilini Examples of the silane derivatives include 3-aminopropyltrimethoxysilane, vinyltrimethoxysilane, octadecyldimethyl[3-(trimethoxysilyl)propyl]ammonium chloride, r-chloropropylmethyldimethoxysilane, methyltrichlorosilane, dimethyldichlorosilane, trimethylchlorosilane, allyltriethoxysilane, 3-aminopropylmethyldiethoxysilane, 3-aminopropyltrimethoxysilane, dimethyldiethoxysilane, 1,3-divinyltetramethyldisilazane, and methacryloxyethyldimethyl(3-trimethoxysilylpropyl)ammonium chloride, and two or more of these may be used in combination. Commercially available products of the silane coupling agent include AY43-059, SR6020, SZ6023, SH6026, SZ6032, SZ6050, AY43-310M, SZ6030, SH6040, AY43-026, AY43-031, sh6062, Z-6911, sz6300, sz6075, sz6079, sz6083, sz6070, sz6072, Z-6721, AY43-004, Z- 6187, AY43-021, AY43-043, AY43-040, AY43-047, Z-6265, AY43-204M, AY43-048, Z-6403, AY43-206M, AY43-206E, Z6341, AY43-210MC, AY43-083, AY43-101, AY43-013, AY43-158E, Z-6920, Z-6940 (manufactured by Toray Silicones), etc. The amount of the silane coupling agent added is preferably 0.1 to 10% by mass relative to the silicone resin. If the amount of the silane coupling agent added is less than 0.1% by mass, the adhesion between the core particles or the conductive fine particles and the silicone resin decreases, and the coating layer may fall off during long-term use. If the amount of the silane coupling agent added is more than 10% by mass, filming of the toner may occur during long-term use.
[0028] Examples of the condensation polymerization catalyst include titanium-based catalysts, tin-based catalysts, zirconium-based catalysts, and aluminum-based catalysts. Among these, titanium-based catalysts are preferred, and titanium diisopropoxybis(ethylacetoacetate) is more preferred, because they have a large effect of promoting the condensation reaction of silanol groups and are less likely to be deactivated. The content of the condensation polymerization catalyst is not particularly limited and can be appropriately selected depending on the purpose.
[0029] <Other ingredients> The other components are not particularly limited as long as they are used in ordinary carriers, and can be appropriately selected depending on the purpose. The content of the other components is not particularly limited and can be appropriately selected depending on the purpose.
[0030] <Carrier properties> The average thickness of the coating layer is preferably 0.05 μm to 1.00 μm, more preferably 0.2 μm to 0.7 μm. If the average thickness is 0.05 μm or more, the coating layer becomes easily broken during use, and the problem of the film being scraped off can be prevented, while if the average thickness is 1.00 μm or less, since the coating layer is not a magnetic material, there is a risk of carrier adhesion occurring on the image, and the problem of the resistance adjustment effect being difficult to fully exert can be prevented.
[0031] The unevenness of the coating layer is determined by the ratio of the average thickness of the coating layer to the standard deviation of the thickness of the coating layer in the carrier. (Standard deviation of coating thickness (s) / average coating thickness (m)) It can be expressed as follows: The ratio (s / m) is preferably 0.05 to 0.60, and more preferably 0.20 to 0.40. If the ratio (s / m) is 0.05 or more, the toner may adhere to the carrier surface, causing a decrease in charging performance. Z It is advantageous in that it is easy to suppress deterioration of image quality, and when it is 0.60 or less, the unevenness between the thin and thick parts of the carrier coating film is small, and there are not a few parts with thin coating film thickness that become leak areas. Examples of methods for adjusting the ratio (s / m) include a method of adjusting the content of the solvent when forming the coating layer, a method of adjusting the heating temperature when forming the coating layer, and the like.
[0032] The ratio (s / m) can be measured by the following method. The carrier and embedding resin (two-part mixture, 30-minute curing epoxy resin, Devcon) are mixed, left to harden overnight, and a rough cross-sectional sample is prepared by mechanical polishing. The cross-section is then polished using a cross-section polisher (SM-09010, JEOL) at an accelerating voltage of 5.0 kV and a beam current of 120 μA. This is then photographed using a scanning electron microscope (Merlin, Carl Zeiss) at an accelerating voltage of 0.8 kV and a magnification of 30,000 times. Using image analysis software (Image-Pro Plus, manufactured by Media Cybernetics), the average thickness of the coating layer is measured at 50 points on the cross section of one carrier particle. The average thickness of this coating layer is measured for 100 grains, the average thickness (m) and the standard deviation s of the coating layer thickness are calculated, and the ratio (s / m) of the average thickness to the standard deviation of the thickness is determined.
[0033] (Method of manufacturing carrier for electrostatic latent image developer) The method for producing a carrier for an electrostatic latent image developer of the present invention is a method for producing the above-mentioned carrier for an electrostatic latent image developer. The method for producing a carrier for an electrostatic latent image developer includes a method for coating the core particles with a coating layer liquid.
[0034] The coating layer liquid contains a compound, and preferably contains a resin, and further contains other components as necessary. The compounds that can be used are the same as the solvents described above, and the resins and other components that can be used are the same as those described above.
[0035] The content of the compound is preferably 20% by mass to 60% by mass based on the total coating layer liquid. When the content of the compound is within the above range, the average thickness of the coating layer can be made uniform.
[0036] The method for coating the core particles with the coating layer liquid is not particularly limited as long as it is a commonly used coating method and can be appropriately selected depending on the purpose. For example, a tumbling fluidized bed method using a spray, a method in which the core particles are immersed in a dispersion liquid and the solvent is dried, etc. can be mentioned.
[0037] (Two-component developer) The two-component developer of the present invention contains the above-mentioned carrier of the present invention and a toner.
[0038] <Toner> The toner contains at least a binder resin, and further contains other components such as a colorant, a charge control agent, and a release agent, if necessary.
[0039] The toner may be any of clear toner, monochrome toner, and color toner. The clear toner is a toner that does not contain a colorant.
[0040] In order to apply the toner to an oil-less system in which oil for preventing toner adhesion is not applied to the fixing roller, the toner may contain a release agent. Although such toners are generally prone to filming, the carrier of the present invention can suppress filming, and therefore the developer of the present invention can maintain good quality for a long period of time.
[0041] Furthermore, color toners, particularly yellow toners, generally have a problem of color staining due to scraping of the carrier coating layer, but the developer of the present invention can suppress the occurrence of color staining.
[0042] The toner can be produced by a known method such as a pulverization method or a polymerization method. For example, when producing a toner by a pulverization method, a melt-kneaded product obtained by kneading toner materials is first cooled, pulverized, and classified to produce base particles. Next, in order to further improve transferability and durability, an external additive is added to the base particles to produce a toner.
[0043] In this case, the device for kneading the toner materials is not particularly limited, but examples thereof include a batch-type twin-roll mixer; a Banbury mixer; continuous twin-screw extruders such as a KTK type twin-screw extruder (manufactured by Kobe Steel, Ltd.), a TEM type twin-screw extruder (manufactured by Toshiba Machine Co., Ltd.), a twin-screw extruder (manufactured by KCK Corporation), a PCM type twin-screw extruder (manufactured by Ikegai Iron Works Co., Ltd.), and a KEX type twin-screw extruder (manufactured by Kurimoto Iron Works Co., Ltd.); and continuous single-screw kneaders such as a Co-Kneader (manufactured by Buss).
[0044] In addition, when pulverizing the cooled molten kneaded product, it can be roughly pulverized using a hammer mill, a rotoplex, etc., and then finely pulverized using a fine pulverizer using a jet stream, a mechanical fine pulverizer, etc. It is preferable to pulverize the product to an average particle size of 3 μm to 15 μm. Furthermore, when classifying the pulverized melt-kneaded product, an air classifier etc. can be used. Note that it is preferable to classify the base particles so that the average particle size is 5 μm to 20 μm. Furthermore, when the external additive is added to the base particles, the external additive is adhering to the surface of the base particles while being disintegrated by mixing and stirring using a mixer or the like.
[0045] <<Binding resin>> The binder resin is not particularly limited, and examples thereof include homopolymers of styrene and its substitutes, such as polystyrene, poly-p-styrene, and polyvinyltoluene; styrene-p-chlorostyrene copolymers, styrene-propylene copolymers, styrene-vinyltoluene copolymers, styrene-methyl acrylate copolymers, styrene-ethyl acrylate copolymers, styrene-methacrylic acid copolymers, styrene-methyl methacrylate copolymers, styrene-ethyl methacrylate copolymers, styrene-butyl methacrylate copolymers, styrene-α-chloromethyl methacrylate copolymers, styrene-acrylonitrile copolymers, styrene-vinyl methyl ether copolymers, styrene-vinyl methyl ketone copolymers, styrene-butadiene copolymers, styrene-isoprene copolymers, and styrene-maleic acid ester copolymers; polymethyl methacrylate, polybutyl methacrylate, polyvinyl chloride, polyvinyl acetate, polyethylene, polyester, polyurethane, epoxy resins, polyvinyl butyral, polyacrylic acid, rosin, modified rosin, terpene resins, phenolic resins, aliphatic or aromatic hydrocarbon resins, and aromatic petroleum resins, and two or more of these may be used in combination.
[0046] The binder resin for pressure fixing is not particularly limited, and examples thereof include polyolefins such as low molecular weight polyethylene and low molecular weight polypropylene; olefin copolymers such as ethylene-acrylic acid copolymer, ethylene-acrylic acid ester copolymer, styrene-methacrylic acid copolymer, ethylene-methacrylic acid ester copolymer, ethylene-vinyl chloride copolymer, ethylene-vinyl acetate copolymer, and ionomer resin; epoxy resins, polyesters, styrene-butadiene copolymers, polyvinylpyrrolidone, methyl vinyl ether-maleic anhydride copolymers, maleic acid-modified phenolic resins, and phenol-modified terpene resins, and two or more of these may be used in combination.
[0047] <<Other ingredients>> Examples of the other components include colorants, release agents, charge control agents, and external additives.
[0048] -Coloring agent- The colorant (pigment or dye) is not particularly limited, and examples thereof include yellow pigments such as cadmium yellow, mineral fast yellow, nickel titanium yellow, navel yellow, naphthol yellow S, Hansa yellow G, Hansa yellow 10G, benzidine yellow GR, quinoline yellow lake, permanent yellow NCG, and tartrazine lake; orange pigments such as molybdenum orange, permanent orange GTR, pyrazolone orange, Balkan orange, indanthrene brilliant orange RK, benzidine orange G, and indanthrene brilliant orange GK; red iron oxide, cadmium red, permanent red 4R, lithol red, pyrazolone red, watching red calcium salt, lake red D, and brilliant carmine 6B. red pigments such as eosin lake, rhodamine lake B, alizarin lake, brilliant carmine 3B; purple pigments such as fast violet B and methyl violet lake; blue pigments such as cobalt blue, alkali blue, victoria blue lake, phthalocyanine blue, metal-free phthalocyanine blue, partially chlorinated phthalocyanine blue, fast sky blue, indanthrene blue BC; green pigments such as chrome green, chromium oxide, pigment green B, malachite green lake; and black pigments such as azine dyes such as carbon black, oil furnace black, channel black, lamp black, acetylene black, and aniline black, metal salt azo dyes, metal oxides, and composite metal oxides, and two or more of these may be used in combination.
[0049] -Release agent- The release agent is not particularly limited, but examples thereof include polyolefins such as polyethylene and polypropylene, fatty acid metal salts, fatty acid esters, paraffin wax, amide wax, polyhydric alcohol wax, silicone varnish, carnauba wax, and ester wax, and two or more of these may be used in combination.
[0050] -Charge control agent- The charge control agent is not particularly limited, but may be, for example, nigrosine; azine dyes having an alkyl group having 2 to 16 carbon atoms; CIBasic Yellow 2 (CI41000), CIBasic Yellow 3, CIBasic Red 1 (CI45160), CIBasic Red 9 (CI42500), CIBasic Violet 1 (CI42535), CIBasic Violet 3 (CI42555), CIBasic Violet 10 (CI45170), CIBasic Violet 14 (CI42510), CIBasic Blue 1 (CI42025), CIBasic Blue 3 (CI51005), CIBasic Blue 5 (CI42140), CIBasic Blue 7 (CI42595), CIBasic Blue 9 (CI52015), CIBasic Blue 24 (CI52030), CIBasic Blue 25 (CI52025), CIBasic Blue 26 (CI44045), CI Basic Green 1 (CI42040), CI Basic Green 4 (CI42000), and other basic dyes; lake pigments of these basic dyes; quaternary ammonium salts such as CI Solvent Black 8 (CI26150), benzoylmethylhexadecylammonium chloride, and decyltrimethylchloride; dialkyltin compounds such as dibutyl and dioctyl; dialkyltin borate compounds; guanidine derivatives; polyamine resins such as vinyl polymers having amino groups and condensation polymers having amino groups; metal complex salts of monoazo dyes; salicylic acid; metal complexes of dialkylsalicylic acid, naphthoic acid, and dicarboxylic acid with Zn, Al, Co, Cr, Fe, and the like; sulfonated copper phthalocyanine pigments; organic boron salts; fluorine-containing quaternary ammonium salts; calixarene compounds, and the like, may be used in combination of two or more. In addition, for color toners other than black, metal salts of white salicylic acid derivatives, and the like are preferred.
[0051] -External additives- The external additive is not particularly limited, but may be inorganic particles such as silica, titanium oxide, alumina, silicon carbide, silicon nitride, boron nitride, etc.; resin particles such as polymethyl methacrylate particles and polystyrene particles having an average particle size of 0.05 μm to 1 μm obtained by soap-free emulsion polymerization, and may be used in combination of two or more kinds. Among these, metal oxide particles such as silica and titanium oxide whose surfaces are hydrophobized are preferred. Furthermore, by using hydrophobized silica and hydrophobized titanium oxide in combination and increasing the amount of hydrophobized titanium oxide added compared to hydrophobized silica, a toner having excellent charging stability against humidity can be obtained.
[0052] (Replenishing developer) The refill developer is composed of the carrier and toner of the present invention described above. By applying the refill developer to an image forming apparatus that forms an image while discharging excess developer in the developing device, stable image quality can be obtained for an extremely long period of time. In other words, the deteriorated carrier in the developing device is replaced with undeteriorated carrier in the refill developer, and the charge amount is kept stable for a long period of time, resulting in a stable image. This method is particularly effective when printing a large image area. When printing a large image area, the main carrier deterioration is carrier charge deterioration due to toner spent on the carrier, but by using this method, the amount of carrier replenishment is also large when the image area is large, so the frequency of replacing the deteriorated carrier increases. This allows stable images to be obtained for an extremely long period of time.
[0053] The mixing ratio of the replenishment developer is preferably 2 to 50 parts by weight of toner per 1 part by weight of carrier. If the toner is 2 parts by weight or more, the amount of replenishment carrier is too large, resulting in an excessive supply of carrier, and the carrier concentration in the developing device becomes too high, which can prevent the problem of the charge amount of the developer easily increasing. Furthermore, the problem of the development ability decreasing and the image density decreasing due to the increase in the developer charge amount can be prevented. If the amount is 50 parts by weight or less, the carrier ratio in the replenishment developer is low, which can prevent the problem of the carrier being replaced less in the image forming device, making it impossible to expect an effect against carrier deterioration.
[0054] (Process cartridge) The process cartridge is one type of toner containing unit. The toner storage unit refers to a unit having a function of storing toner and storing toner or a developer. Examples of the toner storage unit include a developer storage container, a developing device, and a process cartridge. The developer container refers to a container that contains a developer. The developing device refers to a device that contains a developer and has a means for developing. The process cartridge has an electrostatic latent image carrier, a charging means, a developing means, and a cleaning means, contains a developer, and is detachably mountable to an image forming apparatus. The process cartridge may further include an exposure means.
[0055] An embodiment of a process cartridge according to the present invention will be described with reference to FIG. As shown in FIG. 1, a process cartridge 10 has an electrostatic latent image carrier 11, a charging device 12 for charging the electrostatic latent image carrier, a developing device 13 for developing the electrostatic latent image formed on the electrostatic latent image carrier using the developer set of the present invention to form a toner image, and a cleaning device 14 for removing toner remaining on the electrostatic latent image carrier after the toner image formed on the electrostatic latent image carrier is transferred to a recording medium, and is detachable from the main body of an image forming apparatus such as a copier or printer.
[0056] (Image forming apparatus and image forming method) The image forming apparatus of the present invention has a developer storage container that stores at least one of the two-component developer of the present invention and the replenishment developer of the present invention. The image forming apparatus of the present invention preferably comprises the developer storage container, an electrostatic latent image carrier, a charging means for charging the electrostatic image carrier, an exposure means for forming an electrostatic latent image on the electrostatic latent image carrier, a developing means for developing the electrostatic latent image formed on the electrostatic latent image carrier using the developer of the present invention contained in the developer storage container described above to form a toner image, a transfer means for transferring the toner image formed on the electrostatic latent image carrier to a recording medium, and a fixing means for fixing the toner image transferred to the recording medium, and more preferably further comprises other means appropriately selected as necessary, such as a cleaning means. The means for forming the toner image is not particularly limited and can be appropriately selected depending on the purpose, but a means for forming a toner image by developing with a developer having a magnetic brush formed thereon is preferred.
[0057] The image forming method of the present invention comprises a step of forming an electrostatic latent image on an electrostatic latent image carrier, a step of developing the electrostatic latent image formed on the electrostatic latent image carrier using the two-component developer obtained from the developer storage container of the present invention described above to form a toner image, a step of transferring the toner image formed on the electrostatic latent image carrier to a recording medium, and a step of fixing the toner image transferred to the recording medium, and further comprises other means appropriately selected as necessary, such as a cleaning step. The step of forming the toner image is not particularly limited and may be appropriately selected depending on the purpose, but a step of forming a toner image by developing with a developer having a magnetic brush formed thereon is preferred.
[0058] An embodiment of the image forming apparatus of the present invention will be described with reference to FIG. As shown in FIG. 2, first, the electrostatic latent image carrier 20 is rotated at a predetermined peripheral speed, and the peripheral surface of the electrostatic latent image carrier 20 is uniformly charged to a predetermined positive or negative potential by the charging device 32. Next, the peripheral surface of the electrostatic latent image carrier 20 is exposed by the exposure device 33, and electrostatic latent images are formed one after another. Furthermore, the electrostatic latent images formed on the peripheral surface of the electrostatic latent image carrier 20 are developed by the developing device 40 using at least one of the developer set of the present invention and the replenishment developer set, and a toner image is formed. Next, the toner images formed on the peripheral surface of the electrostatic latent image carrier 20 are transferred one after another to the transfer paper fed from the paper feeder between the electrostatic latent image carrier 20 and the transfer device 50 in synchronization with the rotation of the electrostatic latent image carrier 20. Furthermore, the transfer paper to which the toner image has been transferred is separated from the peripheral surface of the electrostatic latent image carrier 20 and introduced into the fixing device to be fixed, and then printed out as a duplicate (copy) to the outside of the image forming apparatus 100. On the other hand, after the toner image has been transferred, the surface of the electrostatic latent image carrier 20 is cleaned by a cleaning device 60 to remove any remaining toner, and then the surface is neutralized by a discharging device 70 so that the surface can be repeatedly used for image formation. EXAMPLES
[0059] Examples of the present invention will be described below, but the present invention is not limited to these examples. In the following, unless otherwise specified, "parts" means parts by mass, and "%" means % by mass.
[0060] Example 1 25 parts of methyl silicone resin (Toray Dow Corning Silicone Co., Ltd., solid content 25%) with a weight average molecular weight of 15,000 made from bifunctional or trifunctional monomers, 25 parts of acrylic resin (solid content 20%), 1 part of titanium diisopropoxybis(ethylacetoacetate) TC-750 (Matsumoto Fine Chemical Co., Ltd.) as a catalyst, and 0.3 parts of SH6020 (Toray Silicone Co., Ltd.) as a silane coupling agent were diluted with decane (boiling point: 174 ° C) to obtain a coating layer liquid, which is a resin solution with a solid content of 10 wt %. This coating layer liquid was coated on 1,000 parts of ferrite core material using a fluidized bed type coating device, controlling the temperature in the fluidized tank to 60 ° C for 30 minutes, and dried for 5 minutes. The obtained carrier was baked in an electric furnace at 180 ° C for 2 hours to obtain carrier A.
[0061] Example 2 Carrier B was obtained in the same manner as in Example 1, except that the solvent in Example 1 was changed to toluene (boiling point: 111° C.).
[0062] Example 3 Carrier C was obtained in the same manner as in Example 1, except that the solvent in Example 1 was changed to dodecane (boiling point: 216° C.).
[0063] Example 4 Carrier D was obtained in the same manner as in Example 1, except that the solvent in Example 1 was changed to isobutyl acetate (boiling point: 118° C.).
[0064] Example 5 Carrier E was obtained in the same manner as in Example 1, except that the solvent in Example 1 was changed to toluene (boiling point: 111° C.), the temperature in the fluidized bed was controlled at 100° C. for coating and drying.
[0065] Example 6 <Production of inorganic fine particles> 100 g of aluminum oxide (AKP-30, manufactured by Sumitomo Chemical Co., Ltd.) was dispersed in 1 liter of water to prepare a suspension, and this liquid was heated to 70°C. A solution of 135 g of stannic chloride and 4.0 g of phosphorus pentoxide dissolved in 1.7 liters of 2N hydrochloric acid and 12 wt% aqueous ammonia were added dropwise to the suspension over a period of 2 hours and 40 minutes so that the pH of the suspension was 7 to 8. After the addition, the suspension was filtered and washed, and the resulting cake was dried at 110°C. Next, this dried powder was treated in a nitrogen stream at 500°C for 1 hour to obtain inorganic fine particles P1.
[0066] 25 parts of methyl silicone resin (solid content 25%) with a weight average molecular weight of 15,000 made from bifunctional or trifunctional monomers, 25 parts of acrylic resin (solid content 20%), 2 parts of titanium diisopropoxybis(ethylacetoacetate) TC-750 (manufactured by Matsumoto Fine Chemical Co., Ltd.) as a catalyst, 0.3 parts of SH6020 (manufactured by Toray Silicone Co., Ltd.) as a silane coupling agent, and 11 parts by weight of inorganic fine particles (P1) as inorganic fine particles were diluted with decane (boiling point: 174 ° C.) to obtain a coating layer liquid, which is a resin solution with a solid content of 10 wt %. This coating layer liquid was coated on 1,000 parts of ferrite core material using a fluidized bed type coating device, controlling the temperature in the fluidized tank to 60 ° C. for 30 minutes, and dried for 5 minutes. The obtained carrier was baked in an electric furnace at 180 ° C. / 2 hours to obtain carrier F.
[0067] Comparative Example 1 Carrier a was obtained in the same manner as in Example 1, except that the solvent in Example 1 was changed to ethyl acetate (boiling point: 77° C.).
[0068] Comparative Example 2 Carrier b was obtained in the same manner as in Example 1, except that the solvent in Example 1 was changed to triethanolamine (boiling point: 360° C.).
[0069] <Measurement of coating layer> 1.0 g of the obtained carrier was mixed with 0.01 g of embedding resin (two-liquid mixture, 30-minute curing epoxy resin, manufactured by Devcon) and left overnight to harden. The hardened resin was mechanically polished to prepare a cross-sectional sample. The cross-sectional sample obtained was polished using a cross-section polisher (SM-09010, manufactured by JEOL) under conditions of an acceleration voltage of 5.0 kV and a beam current of 120 μA. Next, the cross section was photographed using a scanning electron microscope (Merlin, manufactured by Carl Zeiss) at an accelerating voltage of 0.8 kV and a magnification of 30,000 times. The captured image was imported into a TIFF image, and the thickness of the coating film selected was automatically obtained by selecting the coating layer portion to be measured using image analysis software (Image-Pro Plus, Media Cybernetics). In this way, the thickness of the coating layer was measured at 50 points on the cross section of one carrier particle. The thickness of this coating layer was measured for 100 carrier particles, and the average thickness (m) was calculated by averaging the coating layer thicknesses at 50 positions on the cross section of each of the 100 particles (100 x 50 = 5,000 pieces), and the standard deviation (s) of the thicknesses of the coating layers of these 5,000 pieces was calculated, and the ratio (s / m) of the average thickness to the standard deviation of the thickness was calculated. The measurement results are shown in Table 1.
[0070] <Measurement of compound content in carrier> 50 mg of the obtained carrier was filled into a dedicated cup and inserted into a GCMS (QP-2010, Shimadzu Corporation), and the temperature was raised from an initial temperature of 40°C to 320°C at a rate of 20°C / min to obtain a chromatogram. The obtained chromatogram was analyzed to qualify the compounds contained in the carrier. The compounds that could be qualified were sampled in a sample container with a pinhole, and the temperature was raised at a constant rate using a DSC (DSC7000, Hitachi High-Tech Science Corporation) up to a temperature higher than the end of evaporation, and the boiling point was determined from the endothermic peak due to evaporation. The measurement results are shown in Table 1.
[0071] [Table 1]
[0072] <Toner manufacturing> [Synthesis of polyester resin A] Into a reaction vessel equipped with a thermometer, a stirrer, a cooler, and a nitrogen inlet tube, 443 parts of a bisphenol A PO adduct (hydroxyl value 320 mgKOH / g), 135 parts of diethylene glycol, 422 parts of terephthalic acid, and 2.5 parts of dibutyltin oxide were placed and reacted at 200°C until the acid value reached 10 mgKOH / g, thereby obtaining [Polyester Resin A]. This resin had a Tg of 63° C. and a peak number average molecular weight of 6,000. The peak number average molecular weight was measured by gel permeation chromatography (GPC) using an HLC-8320GPC column (manufactured by Tosoh Corporation). GPC (gel permeation chromatography), a column was stabilized in a heat chamber at 40°C, THF as a solvent was passed through the column at this temperature at a flow rate of 1 mL per minute, and 50 μL to 200 μL of a THF sample solution of the resin adjusted to a sample concentration of 0.05% by mass to 0.6% by mass was injected and measured. In measuring the molecular weight, the molecular weight distribution of the sample was calculated from the relationship between the logarithm value and the count number of a calibration curve prepared using several types of monodisperse polystyrene standard samples. The standard polystyrene sample for preparing the calibration curve was, for example, 6×10 2 , 2.1×10 3 , 4×10 3 , 1.75×10 4 , 5.1×10 4 , 1.1×10 5 , 3.9×10 5 , 8.6×10 5 , 2×10 6 , 4.48×10 6 At least 10 standard polystyrene samples were used, and an RI (refractive index) detector was used.
[0073] [Synthesis of polyester resin B] Into a reaction vessel equipped with a thermometer, a stirrer, a cooler, and a nitrogen inlet tube, 443 parts of a bisphenol A PO adduct (hydroxyl value 320 mgKOH / g), 135 parts of diethylene glycol, 422 parts of terephthalic acid, and 2.5 parts of dibutyltin oxide were placed and reacted at 230°C until the acid value reached 7 mgKOH / g, thereby obtaining [Polyester Resin B]. This resin had a Tg of 65° C. and a peak number average molecular weight of 16,000.
[0074] <Production of toner base particles 1> Polyester resin A 40 parts Polyester resin B 60 parts Carnauba wax (product name: Carnauba wax No. 2, manufactured by Kato Yoko Co., Ltd.) 1 part Carbon black (#44, manufactured by Mitsubishi Chemical Corporation) 15 parts The above toner constituent materials were mixed for 3 minutes at 1,500 rpm using a Henschel mixer (Henschel 20B, manufactured by Mitsui Mining Co., Ltd.), and then kneaded using a single-axis kneader (Miniature Buss-Co Kneader, manufactured by Buss) under the following conditions (set temperatures: inlet 100°C, outlet 50°C, feed rate: 2 kg / Hr) to obtain [toner base particles A1].
[0075] The obtained [toner base particles A1] is kneaded, rolled and cooled, pulverized in a pulverizer, and then crushed in an I-type mill (IDS-2 type manufactured by Japan Pneumatic Co., Ltd.) using a flat impact plate and air pressure of 6.8 atm / cm 2 The mixture was then finely pulverized under a constant pressure (conditions: 0.5 kg / hr, feed rate: 0.5 kg / hr) and further classified (132MP manufactured by Alpine Co., Ltd.) to obtain [toner base particles 1].
[0076] To 100 parts of [toner base particles 1], 1.0 part of hydrophobic silica fine particles (R972, manufactured by Nippon Aerosil Co., Ltd.) was added as an external additive, and mixed in a Henschel mixer to obtain toner particles (hereinafter referred to as [toner 1]).
[0077] <Preparation of developers A to F and a to b> To the obtained carriers A to F and a to b (93 parts), 7.0 parts of [Toner 1] (7.2 μm) were added and stirred for 20 minutes in a ball mill to prepare developers A to F and a to b.
[0078] <Solid carrier adhesion> Using the obtained developers, a running evaluation was carried out. Using the obtained developers A to F and a to b, the solid carrier adhesion was evaluated after running 10,000 sheets and 1,000,000 sheets at an image area ratio of 40% on a digital color copier / printer multifunction machine (RICOH Pro C9100, manufactured by Ricoh Co., Ltd.). The solid image was developed under the specified conditions (charge potential (Vd): -600V, potential after exposure of the image area (solid original): -100V, development bias: DC, -500V), and the image was interrupted by turning off the power during imaging, and the number of carrier particles on the photoconductor after transfer was counted, and the solid carrier adhesion after running 10,000 sheets and 1,000,000 sheets was evaluated based on the following evaluation criteria. The evaluation results are shown in Table 2. The area to be evaluated was a 10 mm x 100 mm area on the photoconductor. In addition, in the following criteria, a rating of △ or higher was acceptable for use. -Evaluation criteria- ◎:0 pieces ○:1~3 pieces △:4~10 pieces ×: 11 or more
[0079] <Cohesiveness> 50±1.0 g of the obtained carrier was weighed out (the weighed mass was designated as m0 (g)), and the weighed carrier was passed through a sieve with openings twice the average particle size (μm) of the core material. The amount of carrier remaining on the sieve (designated as m1 (g)) was used to calculate the value obtained using formula 1 as the cohesiveness, and the cohesiveness was evaluated based on the following evaluation criteria. The evaluation results are shown in Table 2. In the following criteria, samples rated as △ or higher were usable. Formula 1: [(m0)-(m1)] / (m0)×100(%) -Evaluation criteria- ◎: 99% or more ○: 98% or more but less than 99% △: 97% or more but less than 98% ×: Less than 97%
[0080] [Table 2]
[0081] For example, aspects of the present invention are as follows. <1> A carrier for an electrostatic latent image developer, comprising: a magnetic core particle; and a coating layer that coats at least a portion of the surface of the core particle, The carrier for an electrostatic latent image developer is characterized in that it contains a compound having a boiling point of 110°C to 230°C. <2> The compound is a hydrocarbon. <1> 2. A carrier for an electrostatic latent image developer according to claim 1. <3> The ratio of the average thickness of the coating layer to the standard deviation of the thickness of the coating layer. (Standard deviation of coating thickness / average coating thickness) is 0.05 to 0.60. <1> from <2> 10. The electrostatic latent image developer carrier according to claim 9, <4> The coating layer further contains inorganic fine particles. <1> from <3> 10. The electrostatic latent image developer carrier according to claim 9, <5> The above <1> from <4> 2. A two-component developer comprising the carrier for electrostatic latent image developer according to claim 1 and a toner. <6> The above <1> from <4> The replenishing developer is characterized in that it contains 2 to 50 parts by mass of a toner per part by mass of the carrier for electrostatic latent image developer described in any one of the above. <7> an electrostatic latent image carrier; and a charging means for charging the surface of the electrostatic latent image carrier; The electrostatic latent image formed on the electrostatic latent image carrier is <5> A developing means for developing using the two-component developer described in a cleaning means for cleaning the toner remaining on the surface of the electrostatic latent image carrier; The process cartridge is characterized by having the following features. <8> The above <5> The two-component developer according to claim 1, <6> 2. An image forming apparatus comprising a developer container that contains at least one of the replenishment developers described above. <9> forming an electrostatic latent image on an electrostatic latent image carrier; The electrostatic latent image formed on the electrostatic latent image carrier is <5> forming a toner image by developing the toner image with the two-component developer according to transferring the toner image formed on the electrostatic latent image carrier onto a recording medium; and fixing the toner image transferred onto the recording medium. <10> This is a method for producing a carrier for an electrostatic latent image developer, characterized in that a coating layer is formed by coating the surfaces of magnetic core particles with a coating layer liquid containing a compound having a boiling point of 110°C to 230°C.
[0082] The above <1> from <4> The carrier for electrostatic latent image developer according to any one of the preceding claims. <5> The two-component developer according to <6> The replenishing developer according to <7> The process cartridge according to the <8> The image forming apparatus according to the <9> The image forming method according to claim 1, <10> According to the method for producing a carrier for an electrostatic latent image developer described above, the conventional problems can be solved and the object of the present invention can be achieved. [Explanation of symbols]
[0083] 10 Process cartridge 11 Photoreceptor 12 Charging device 13 Developing device 14 Cleaning device [Prior art documents] [Patent documents]
[0084] [Patent Document 1] Japanese Patent Application Publication No. 6-250443 [Patent Document 2] Patent No. 4972537
Claims
1. A carrier for an electrostatic latent image developer, comprising: a magnetic core particle; and a coating layer that coats at least a portion of the surface of the core particle, the carrier for the electrostatic latent image developer contains at least one of butyl acetate, isobutyl acetate, octane, diethylbenzene, xylene, decane, and dodecane; a ratio of an average thickness of the coating layer to a standard deviation of the thickness of the coating layer (standard deviation of the thickness of the coating layer / average thickness of the coating layer) is 0.20 to 0.
60.
2. 2. The carrier for an electrostatic latent image developer according to claim 1, wherein the coating layer further contains inorganic fine particles.
3. 3. A two-component developer comprising the carrier for electrostatic latent image developer according to claim 1 and a toner.
4. 3. A replenishing developer comprising 2 to 50 parts by weight of a toner per 1 part by weight of the carrier for electrostatic latent image developer according to claim 1.
5. an electrostatic latent image carrier; and a charging means for charging the surface of the electrostatic latent image carrier; a developing means for developing the electrostatic latent image formed on the electrostatic latent image carrier by using the two-component developer according to claim 3; a cleaning means for cleaning the toner remaining on the surface of the electrostatic latent image carrier; A process cartridge comprising:
6. 5. An image forming apparatus comprising a developer containing unit containing at least one of the two-component developer according to claim 3 and the replenishment developer according to claim 4.
7. forming an electrostatic latent image on an electrostatic latent image carrier; a step of developing the electrostatic latent image formed on the electrostatic latent image carrier with the two-component developer according to claim 3 to form a toner image; transferring the toner image formed on the electrostatic latent image carrier onto a recording medium; and fixing the toner image transferred onto the recording medium.
8. A method for producing a carrier for an electrostatic latent image developer according to any one of claims 1 to 2, comprising the steps of: A method for producing a carrier for an electrostatic latent image developer, comprising coating the surfaces of magnetic core particles with a coating layer liquid containing at least one of butyl acetate, isobutyl acetate, octane, diethylbenzene, xylene, decane, and dodecane to form a coating layer.
Citation Information
Patent Citations
JP1974072537A
Color developer
JP1994250443A
Image forming apparatus
JP2006058639A
Carrier, method for producing same, developer, and image forming method
JP2007072444A
Carrier and method for manufacturing the same, and developer and image forming method
JP2008145571A